Ways of Tash-heer and the method of outweighing for Khalîl Ibn Is’hâq Al-Mâliki, according to his book Al-Mukhtassar - ben harzallah, abdelkader; saadoune, kadour (Journal of Social Sciences and Humanities, 2021)
Mukhtassar Sidi Khalil Ibn Ishaq Al-Maliki is characterised by quality and mastery. It is considered as one of the most renowned Maliki books, and people have concentrated on studying, understanding, and memorizing it. The most important thing that he focused on is his presentation of jurisprudential differences in the school, as well as the well-known opinion, which has the fatwa, while trying to collect as many issues and branches as possible, to be brief, and to focus on technical terms. Thus, the present research examines methods of the well-know and weighing methods in Khalil bin Isaac El-Djendi. The work is divided into three chapters and a conclusion. It deals with the definition of the well-known and the preponderant, the fruits of difference in finding the well-known and the preponderant in Maliki School. It also clarifies weighing methods when there is opposition between the well-known and the preponderant revealing three main stands: weighing stand, silence stand, and non-weighing stand. The research also highlighted the different terms of the well-known used by Sidi Khalil for himself and for others. Among these terms are the chosen, the most prominent, the most correct, the best, etc. The findings revealed that Sidi Khalil has a specific doctrine in dealing with jurisprudential issues following on Imam Malik, with renewal in methods so as to arrive at the preponderant and the well-known that correspond with evidence.2